Gastrointestinal nematode infections in sheep raised in Botucatu, state of Sao Paulo, Brazil - Wilmsen, Maurício Orlando [UNESP]; Silva, Bruna Fernanda; Bassetto, César Cristiano [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
Gastrointestinal nematode infections were evaluated in sheep raised in Botucatu, state of Sao Paulo, Brazil between April 2008 and March 2011. Every month, two tracer lambs grazing with a flock of sheep were exposed to natural infection with gastrointestinal nematodes for 28 consecutive days. At the end of this period, the lambs were sacrificed for worm counts. Haemonchus contortus presented 100% of prevalence. The seasons exerted no significant influence on the mean intensity of H. contortus, which ranged from 315 worms in November 2010 to 2,5205 worms in January 2011. The prevalence of Trichostrongylus colubriformis was also 100%, with the lowest mean intensity (15 worms) recorded in February 2011 and the highest (9,760 worms) in October 2009. In the case of T. colubriformis, a significant correlation coefficient was found between worm counts vs. rainfall (r = -0.32; P < 0.05). Three other nematodes species were found in tracer lambs, albeit in small numbers. Their prevalence and mean intensity (in parenthesis) were as follows: Oesophagostomum columbianum 28% (25.2), Cooperia curticei 7% (4.5) and Trichuris spp. 2% (1). In conclusion, the environmental conditions of the area proved to be highly favorable for the year-round transmission of H. contortus and T. colubriformis.

A ocorrência de infecções por nematódeos gastrintestinais foi avaliada de abril de 2008 até março de 2011em ovinos criados em Botucatu, estado de São Paulo. Todos os meses, dois cordeiros traçadores foram expostos à infecção natural por nematódeos gastrintestinais, durante 28 dias consecutivos, ao pastejar junto com um rebanho de ovelhas. Ao final desse período, os animais foram sacrificados para a identificação e quantificação dos helmintos. Haemonchus contortus apresentou prevalência de 100%. Não houve influência significativa das estações do ano na intensidade média de H. contortus, que variou de 315 vermes em novembro/2010 a 25.205 vermes em janeiro/2011. Trichostrongylus colubriformis também apresentou prevalência de 100% com a menor intensidade média (15 vermes) em fevereiro/2011 e a maior (9.760 vermes) em outubro/2009. No caso de T. colubriformis, houve correlação significativa entre as contagens de vermes x precipitação (r = −0,32; P <0,05). Outras três espécies de nematódeos foram encontradas nos cordeiros traçadores, no entanto em pequenas quantidades, com as seguintes prevalências e intensidades médias (entre parênteses): Oesophagostomum columbianum 28% (25,2), Cooperia curticei 7% (4,5) e Trichuris spp. 2 % (1). Em conclusão, as condições ambientais da área foram muito favoráveis durante todo o ano para a transmissão de H. contortus e T. colubriformis.
Infecções por nematódeos gastrintestinais em ovinos criados em Botucatu, estado de São Paulo, Brasil
Keywords: Haemonchus contortus; Trichostrongylus colubriformis; Tracer lamb; Nematode burden; Seasonal variation; Haemonchus contortus; Trichostrongylus colubriformis; Cordeiro traçador; Carga parasitária; Variação sazonal